المخطوطات تراث إنساني ومكسب حضاري.. مكتبات المخطوطات في العالم وفي تونس.. الواقع والآفاق - البوجديدي, علي (مجلة البحرين الثقافية, 2020)
Keywords: Bibliothèques -- Djerba

مكتبات المخطوطات بجزیرة جربة مزارات ثقافیة سیاحیة: مكتبة جامع الترك أنموذجا - يزید, انتظار (المعھد العالي للعلوم الإنسانیة بمدنین, 2020)
Keywords: Bibliothèques -- Djerba

Building Ibadi Manuscript Archives in Tunisia: The Salim b. Ya'qub Library in Djerba - Love Jr, Paul M. ([P4339] Ibadi Archives: Thinking with Spaces from Manuscript Libraries to Digital Repositories, 2020)
Using the example of a recent inventory carried out in 2015 of the private library of the late Ibadi scholar and historian Salim b. Ya’qub (d.1991) in Tunisia, this presentation argues the late 19th and early 20th centuries represent a formative period for many major Ibadi manuscript collections in Tunisia. The Bin Ya’qub library, similar to manuscript collections through the Maghrib, the Sahara, and West Africa, reflects the archive-building travels and efforts of a Muslim scholar during the early 20th century and typifies a broader trend in Northern Africa toward the accumulation of large manuscript collections that today represent the main repositories of primary source material used by historians to write the history of Islam in the region. By offering a brief history of the creation of the Bin Yaq’ub library and the accumulation of its contents, the presentation suggests that thinking of the history of these and other Ibadi manuscript collections in terms of a network of scholars and books, constantly in motion, can help reshape the way historians use the texts of Ibadi archives. In addition, this paper considers the impact of the history of this and other Ibadi libraries in Tunisia on current research on pre-modern and early modern Ibadi history. In short, it considers the ways in which the story of the creation of this 20th century collection influences the ways in which we understand the history of pre-modern Ibadism.
Keywords: Bibliothèques -- Djerba

Manuscripts are like vampires: Libraries and their uncertain histories on the island of Jerba, Tunisia - Love Jr, Paul M. (History Compass, 2020)
Keywords: Bibliothèques -- Djerba